ANALISIS STRATEGI KOMUNIKASI POLITIK I PUTU ALIT YANDINATA PADA PILEG KABUPATEN BADUNG TAHUN 2019 (Jurnal Nawala Politika, 2023)
In a democratic party, it is one of the political phenomena, in which political candidates compete to present various kinds of political communication strategies that can attract people. This study aims to see how the phenomenon of political communication was carried out by I Putu Alit Yandinata, S.S. in the 2019 legislative elections. Alit Yandinata's victory for three periods attracted the attention of researchers in studying the phenomenon of political communication that he carried out during the campaign period. By using a descriptive qualitative method, this study also tries to find out what patterns were used in the campaigns carried out by Alit Yandinata. The results of this study indicate that the use of media can help improve effective political communication, either through social media (such as Facebook, Instagram, Youtube) or conventional media (such as billboards). Apart from that, understanding demographics and a clear target audience supported by party popularity are other aspects that help create an effective political campaign. Keywords: Pemilihan Legislatif, Strategi Komunikasi Politik, Analisis 4P, I Putu Alit Yandinata